Collaboration between the Scrum and third party services in the network organization - Sienkiewicz, Łukasz D. (Kolaboracja pomiędzy Scrumem a usługodawcami zewnętrznymi i wewnętrznymi w organizacji sieciowej, 2012)
Many scientific publications demonstrate the Scrum as the best method for managing software development. Nevertheless, the original Scrum method is not sufficient for managing work in the network organization where stakeholders may know nothing about the Scrum or even Agile. In this paper, we use the 3C model to determine how the teamwork of third party services and other Scrum players looks. We believe that will help in finding a more satisfactory approach for managing software development in a strongly distributed environment (i.e. network organization)
Informatyka Ekonomiczna = Business Economics, 2012, Nr 1 (23), s. 59-66
Keywords: 3C model; agile; collaboration; cooperation; communication; coordination; Scrum; third party service; network organization; software development; kolaboracja; kooperacja; komunikacja; usługodawcy wewnętrzni i zewnętrzni; organizacja sieciowa; wytwarzanie oprogramowania